Promoting agricultural entrepreneurship through practical education in Chinese universities - Wei Hou; Huajian Song; Qianwen Yang; Lei Luo; Jingyi Ding; Yipei Cao; Ruihua Hu; Guo Li; Hai Ma (PLoS ONE, 2026)
The social phenomenon of university students learning agriculture rather than pursuing it, understanding agriculture rather than choosing agriculture, is a major challenge for the sustainable development of agricultural talents in China. This research paper investigates the impact and mechanism of practical education in agricultural schools on students’ intention to start agricultural businesses using OLS, Probit, and mediation effect models. Data from a survey of 1612 Chinese students from Sichuan Agricultural University, Nanjing Agricultural University and other 6 agricultural universities was analyzed, with instrumental variable probit model (IV-Probit) utilized to tackle endogeneity issues. The results showed that (1) The implementation of rural social practice, volunteer service, entrepreneurship competition, and agricultural labor education by universities can significantly boost university students’ interest in starting their agricultural businesses. Additionally, for every additional type of practical education students receive, they are 11.0% more likely to want to start business in agriculture. (2) Practical education will affect individual entrepreneurial effectiveness perception, including economic benefit perception, social status perception and professional value perception. Among these, the mediating effect of professional value perception is the strongest, with a ratio of 16.1%. (3) The results suggest that entrepreneurship support policy play a role in moderating the connection between individuals’ economic benefit, social status perceptions and their intentions. (4) The intentions of university students to start agricultural businesses are significantly correlated with their control variables, including major selection, students cadre experience, agricultural cognition, household registration, and family members’ occupation. Therefore, it is suggested that there should be a focus on enhancing practical education in agricultural universities, fostering students’ confidence in agricultural entrepreneurship, and optimizing sustainable policy support for university students’ entrepreneurial endeavors.